ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA PADA PELAKU USAHA PELANGGARAN HAK CIPTA DI KOTA BATAM - Purba, Ervanny; Jamba, Padrisan (SCIENTIA JOURNAL, 2021)
This study aims to identify and understand the criminal liability for copyright infringement perpetrators in the form of pirated VCD/DVDs in Batam City and the police in taking action against copyright infringement committed by business actors. The development of science and technology has changed the times so that it has an impact on the behavior of every human being in the business world, where currently many other people's works are recognized as their own of course, this is very contrary to the rules of positive law that apply in Indonesia. Copyright infringement in the trade sector can be exemplified such as counterfeiting, copying and, piracy that many business actors (producers) have. Criminal a liability to determine a criminal act against whether or not a perpetrator of the act against a criminal act that has been committed. In criminal liability there is a principle, namely not being punished if there is no mistake (geen straf zonder schuId; Actus non facit reum nisi mens sir rea). It can be interpreted that a person can be punished, then that person has not only committed a crime but also there is no mistake in his actions and also a perpetrator of the criminal act has fulfilled the ability to take responsibility.